Drop-Out School Phenomenon from Social Perspective at Gunung Batu Village, Pulau Beringin Sub-District, South Oku District - Wiwik Handayani; Shomedran Shomedran (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This study aims to study amd explain the phenomenon of School Dropout seen from the Social Aspects in Gunung Batu Village, Pulau Beringin District. This study uses a descriptive method with a qualitative approach. The informants in this study may be five people. The data technique used was interview research subjects. The data analysis techniques used were data, data reduction, data presentation, and data retrieval. Based on the results of data analysis carried out through the triangulation method, it can be concluded that the phenomenon of children dropping out of school is seen from social aspects, social aspects of society and aspects of children's social behavior. Social aspects of society, namely children dropping out of school are more concerned with working as farmers to earn their own money to continue their education, aspects of social behavior of children dropping out of school besides working to earn their own money, dropping out children also do habits in the community, namely playing, hanging out on the roadside, sports and gather with friends in the community.Key words: children, droping out of school, social aspe